Launching workshop of new research initiative to address challenges facing Mali’s small ruminant value chain - Maiga, Assoumane (CGIAR System Organization, 2022)
Co-creation, with stakeholders, of the SAPLING vision and theory of change for the small ruminant value chain in Mali